Factors associated with congenital anomalies in Addis Ababa and the Amhara Region, Ethiopia: a case-control study - Molla Taye; Mekbeb Afework; Wondwossen Fantaye; Ermias Diro; Alemayehu Worku (BMC Pediatrics, 2018)
Abstract Background The early stage of embryo development is extremely vulnerable to various teratogenic factors, leading to congenital anomalies. In Ethiopia, a significant number of babies are born with congenital anomalies, but the risk factors for the anomalies have never been studied. Understanding the specific risk factors for congenital anomalies is very essential to provide health education that aims at creating awareness and establishing preventive strategic plan/s. The main objective of this study was to assess the risk factors associated with congenital anomalies in Addis Ababa and the Amhara Region, Ethiopia. Methods A case-control study was conducted from January 1- June 30, 2015. The participants were recruited at the purposively selected hospitals in Addis Ababa and the Amhara Region. A total of 207 cases and 207 controls were included in the study. Cases were neonates, infants, and children 0-11 months of age with external and internal major congenital anomalies diagnosed by pediatricians. Controls were neonates, infants, and children 0-11 months of age without external and internal anomalies. Data on sociodemographic characteristics, exposure to risk factors, and reproductive history were collected by face to face interviews with children’s mothers/caregivers using a structured questionnaire. Binary logistic regression was employed to explore risk factors associated with the occurrence of the problems. Results About 87.4% of the children were below 6 months, and 12.6% were between 6 and 11 months. The majority (59.9%) of the children were male, with the M: F sex ratio of 1.49. The mean age of the mothers was 26 years (16-45 years). Unidentified medication use during early pregnancy (AOR = 4.595; 95% CI: 1.868-11.301, P-value = 0.001), maternal alcohol drinking (AOR = 2.394; 95% CI: 1.212-4.726, P-value = 0.012), and exposure to chemicals (AOR = 9.964; 95% CI = 1.238-80.193, P-value = 0.031) were significantly associated with the occurrence of congenital anomalies. Iron folate use (AOR = 0.051; 95% CI: 0.010-0.260, P-value = < 0.001) before and during early pregnancy had a protective effect on congenital anomaly. Conclusion Unidentified medication use, alcohol drinking during early pregnancy, and exposure to chemicals had a significant association with the occurrence of congenital anomalies, whereas iron folate use before and during early pregnancy had a protective effect from congenital anomalies.